Inter-limb strength asymmetry in adolescent distance runners: Test-retest reliability and relationships with performance and running economy - Blagrove, R. C.; Bishop, C.; Howatson, G.; Hayes, P. R. (Journal of Sports Sciences, 2021)
The purpose of this investigation was, firstly, to quantify the test-retest reliability of strength measures in adolescent distance runners; and secondly, to explore the relationships between inter-limb strength asymmetry and performance and running economy (RE) in a similar cohort of young runners. For the reliability study, twelve (n = 6 female) post-pubertal adolescent distance runners performed an isometric quarter-squat on a dual force plate and unilateral isometric hip extension and hip abduction tests on two occasions. For the correlation study, participants (n = 31) performed the strength tests plus a submaximal incremental running assessment and a maximal running test. Running economy was expressed as the average energy cost of running for all speeds below lactate turnpoint and was scaled for body mass using a previously calculated power exponent. Allometrically scaled peak force during the quarter-squat and peak torque in the hip strength tasks showed acceptable levels of reproducibility (typical error =6.3%). Relationships between strength asymmetry and performance and RE were low or negligible (r < 0.47, p > 0.05), except for hip abduction strength asymmetry and RE in the female participants (r = 0.85, p < 0.001, n = 16). Practitioners should consider inter-limb hip abduction strength asymmetry on an individual level, and attempting to reduce this asymmetry in females may positively impact RE.